The Relationship between Knowledge Level and Medication Adherence Among Hypertensive Patients in Pekuncen Village - Zulfa Rofiqoh; Pramesti Dewi; Siti Haniyah (LPPM Universitas Harapan Bangsa, 2024)
Hypertension is a non-communicable disease that is sometimes encountered in healthcare services and can cause problems in the health sector. A common problem is non-adherence of patients to taking medications due to a lack of knowledge. The purpose of this study was to determine the relationship between knowledge level and medication adherence among hypertensive patients in Pekuncen Village. This quantitative study utilized a correlational research design with a cross sectional approach and purposive sampling technique with a sample of 71 hypertensive patients. Data was collected using a knowledge questionnaire and the MMAS-8. This study showed that the knowledge level was moderately adequate (45.1%) and medication adherence was moderate (40.8%). Analysis using the Spearman rank statistical test resulted in an r value of 0.661 indicating a strong relationship between the two variables. The p value was <0.001, meaning there is a relationship between knowledge level and medication adherence among hypertensive patients in Pekuncen Village.